Development of a Wireless Gateway for Industrial Internet of Things Applications - Ferreira, Israel Vieira [UNESP]; Bigheti, Jeferson Andre; Godoy, Eduardo Paciencia [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Industry 4.0 is a new concept representing the evolution of the current production systems through the convergence of new technologies of industrial automation and information systems. The Industrial Internet of Things (IIoT) stands out for the communication among equipment and systems, offering to users a variety of useful information for the management of improvement of production systems. This paper presents the development of a wireless gateway for IIoT applications. This IIoT gateway is based on open source solutions and enables the programming, network communication and supervision of the industrial equipment. The communication protocols supported by the gateway are: Modbus TCP/IP, MQTT and CoAP for connection between the remote modules and the gateway and HTTP using the REST standard with JSON format for external communication with the gateway. An innovation and differential of the gateway was adding the OpenPLC project in order to enable the programming and automation of industrial processes according to the IEC 61131-3. In addition, the gateway stores process information and makes it available online and accessible in real-time to any point connected to the network and/or the Internet. Several operation tests performed validated the development and demonstrated the efficacy of the gateway.
Keywords: Embedded Devices; Industry 4.0; Internet of Things; OpenPLC